Homogenization in Species Composition and No Change in Aboveground Biomass Across Tibetan Permafrost Regions Over Ten Years - Yang, Yan; Klanderud, Kari; Yang, Yinghui; Jin, Huaan; Lu, Yaqiong; Zhang, Tongzuo; Wang, Genxu (Frontiers in Environmental Science, 2022)
The Tibetan Plateau is the most extensive high-elevation grassland on earth, with the largest expanse of high-elevation permafrost. It is experiencing climate warming that is projected to continue at rates above the global mean, potentially jeopardizing ecosystem functioning. We conducted a broad scale resampling project in the permafrost region of Tibet to examine if plant production and diversity had changed over time. We recorded vascular plant species occurrences and harvested aboveground biomass at 36 alpine grassland sites in 2008 and 2018. Our results show that aboveground biomass increased for legumes and forbs, but decreased for grasses and sedges, resulting in no overall change in aboveground biomass during the ten years period. Our results indicate that functional group abundance may shift from grasses and sedges towards more legumes and forbs, and that species composition is becoming more similar between grassland types, and thus beta diversity is decreasing in the permafrost region of Tibet.